The Role of Regional Planning in Urban Transformation - Milanie, Feby (International Conference on Sciences Development and Technology, 2023)
The rapid and dynamic development of cities requires the strategic role of regional planning in carrying out urban transformation. This research aims to investigate and analyze the role that regional planning plays in the urban transformation process, focusing on the aspects of planning that influence sustainable and competitive urban development. The research methodology involves literature analysis, case studies of cities that have undergone successful transformation, as well as interviews with urban planning experts. The results show that regional planning plays a key role in steering urban transformation towards sustainable development. It facilitates efficient infrastructure development, planned land use management, and improved environmental quality and community welfare. It also plays a role in formulating policies that support economic growth, community empowerment, and the creation of inclusive public spaces. Case studies show that the integration of regional planning with various local, regional and national stakeholders has a positive impact in addressing urban challenges. Therefore, close collaboration between the government, private sector and civil society is required to create a holistic and sustainable regional planning strategy. This research contributes to further understanding of the role of regional planning in the context of urban transformation and provides a framework for policy development that supports sustainable and competitive urban growth. The implications of this research provide direction for policy makers, urban planners and related parties to enhance the role of regional planning as a key to success in facing the challenges of modern urban transformation.